0\Rightarrow4,3-0,4(n-1)>0\\ \\-0,4(n-1)>-4,3\\ \\n-1 < 10,75\\ \\n<11,75\\\\n=11" alt="a_{1}=4,3;\\a_{2}=3,9\\d=a_{2}-a_{1}=3,9-4,3=-0,4\\\\a_{n}=a_{1}+d(n-1)\\ \\a_{n}=4,3-0,4(n-1)\\ \\a_{n}>0\Rightarrow4,3-0,4(n-1)>0\\ \\-0,4(n-1)>-4,3\\ \\n-1 < 10,75\\ \\n<11,75\\\\n=11" align="absmiddle" class="latex-formula">
![S_{n}=\frac{(2a_{1}+d(n-1))n}{2}\\ \\S_{11}=\frac{(2\cdot4,3-0,4*(11-1))\cdot11}{2}=25,3 S_{n}=\frac{(2a_{1}+d(n-1))n}{2}\\ \\S_{11}=\frac{(2\cdot4,3-0,4*(11-1))\cdot11}{2}=25,3](https://tex.z-dn.net/?f=S_%7Bn%7D%3D%5Cfrac%7B%282a_%7B1%7D%2Bd%28n-1%29%29n%7D%7B2%7D%5C%5C%20%5C%5CS_%7B11%7D%3D%5Cfrac%7B%282%5Ccdot4%2C3-0%2C4%2A%2811-1%29%29%5Ccdot11%7D%7B2%7D%3D25%2C3)